Structural validity and reliability of the integrated conflict and violence scale - Mutto, Milton; Lawoko, Stephen; Ovuga, Omilio; Bangdiwalad, Shrikant (International journal of injury control and safety promotion, 2010)
The study validated structure stability, reliability and sub-scale distinctiveness of integrated conflict and violence scale (ICVS) and was cross-sectional; war-affected grade 5 school children participated. ICV internal factorial validity and reliability were evaluated; eigenvalue size and scree plots were used for factor selection. A variable retention factor load threshold of 40.30 was used: Cronbach’s a tests confirmed reliability increments. Pair-wise Pearson correlation tests evaluated sub-scale distinctiveness. Gulu University granted ethical clearance. A total of 280 grade 5 children from 50 primary schools participated: 53% of them were males. Two factors accounted for 100% of variability in attitudes; 18 variables were retained. Expelled variables were: ‘If I catch some one stealing my sugar cane I will fight’ and ‘a bully should be forgiven’. Sub-scale internal consistency reliability coefficients were 0.73 and 0.65, respectively and distinctiveness correlation coefficient was 70.06. The ICVS was validated using standard criteria. Emerging two-factor scale has acceptable psychometric properties especially factorial structure, internal consistency and sub-scale distinctiveness.
Keywords: Conflict; Violence; Scale